Crises, Creditors and Cramdowns: An evaluation of the protection of minority creditors under the WHOA in light of Directive (EU) 2019/1023 - Hidde Volberda (Utrecht University School of Law, 2021)
Covid-19 has severe economic consequences, leading to an increasing amount of businesses facing overwhelming debts. Since the financial crisis of 2008 the European Union has taken on a more rescue-oriented approach towards bankruptcy, resulting in Directive (EU) 2019/1023. This Directive creates a framework for pre-insolvency restructuring, thereby avoiding unnecessary bankruptcies. Accordingly, pre-insolvency restructuring is a valuable instrument in mitigating the negative economic effects of Covid-19. The Netherlands has recently adopted the Act on the Confirmation of Private Plans (WHOA), National Legislation on pre-insolvency restructuring. In order to balance the rights of secured and unsecured creditors the 20%-rule was adopted. This rule guarantees small-scale Small-to-Midsized (SME)-creditors the right to satisfaction of 20% of their claims in restructuring proceedings. In this paper, I evaluate whether the 20%-rule is in accordance with the Directive. I argue that the 20%-rule is in line with the Directive, but that the overly restrictive system of judicial review under the WHOA hampers its application in practice. Therefore, the Dutch legislator should allow for more room for judicial interpretation on the suitability of the application of the 20%-rule. This more nuanced approach better aligns the 20%-rule with the European Restructuring Directive.